Father-child dyads exhibit unique inter-subject synchronization during co-viewing of animation video stimuli - Azhari, Atiqah; Bizzego, Andrea; Esposito, Gianluca (Social neuroscience, 2021)
Inter-subject synchronization reflects the entrainment of two individuals to each other's brain signals. In parent-child dyads, synchronization indicates an attunement to each other's emotional states. Despite the ubiquity with which parents and their children watch screen media together, no study has investigated synchronization in father-child dyads during co-viewing. The present study examined whether father-child dyads would exhibit inter-subject synchronization that is unique to the dyad and hence would not be observed in control dyads (i.e., randomly paired signals). Hyperscanning fNIRS was used to record the prefrontal cortex (PFC) signals of 29 fathers and their preschool-aged children as they co-viewed children's shows. Three 1-min videos from "Brave", "Peppa Pig" and "The Incredibles" were presented to each dyad and children's ratings of video positivity and familiarity were obtained. Four PFC clusters were analyzed: medial left, medial right, frontal left and frontal right clusters. Results demonstrated that true father-child dyads showed significantly greater synchronization than control dyads in the medial left cluster during the emotionally arousing conflict scene. Dyads with older fathers displayed less synchrony and older fathers, compared to younger ones, exhibited greater activity. These findings suggest unique inter-subject synchronization in father-child dyads during co-viewing which is potentially modulated by parental age.